Ornithine decarboxylase functions in both autophagy and apoptosis in response to ultraviolet B radiation injury - Liu, Yi‐Liang; Hsiao, I‐Hsin; Lin, Yen‐Hung; Lin, Chih‐Li; Jan, Ming‐Shiou; Hung, Hui‐Chih; Liu, Guang‐Yaw (Journal of cellular physiology, 2022)
We present a mechanism for how ornithine decarboxylase (ODC) regulates the crosstalk between autophagy and apoptosis. In cancer cells, low‐intensity ultraviolet B (UVBL) induces autophagy while high‐intensity UVB (UVBH) induces apoptosis. Overexpression of ODC decreases UVBL‐induced autophagy by inhibiting Atg5‐Atg12 conjugation and suppressing the expression of autophagy markers LC3, Atg7, Atg12, and BECN1 proteins. In contrast, when ODC‐overexpressing cells are exposed to UVBH radiation, the levels of LC3‐II, Atg5‐Atg12 conjugate, BECN1, Atg7, and Atg12 increase, while the apoptosis marker cleaved‐PARP proteins decrease, indicating that ODC overexpression induced UVBH‐induced autophagy but inhibited UVBH‐induced cellular apoptosis. Additionally, when exposed to UVBH radiation, silencing BECN1, Atg5, and Atg12 genes results in a decrease in the level of LC3‐II proteins but an increase in the level of cleaved‐PARP proteins, and apoptotic bodies were significantly increased while autophagosomes were significantly decreased. These findings imply that ODC inhibits apoptosis in cells via the autophagy pathway. The role of Atg12 in ODC‐overexpressing cells exposed to UVBH radiation is investigated using site‐directed mutagenesis. Our results indicate that the Atg12‐D111S mutant has increased cell survival. The Atg12‐ΔG186 mutant impairs autophagy and enhances apoptosis. We demonstrate that when ODC‐overexpressing cells are silenced for the Atg12 protein, autophagy and apoptosis are strongly affected, and ODC‐induced autophagy protects against UVBH‐induced apoptosis via the Atg12 protein. Ornithine decarboxylase (ODC) functions in two distinct ways in response to ultraviolet B (UVB)‐induced injury. ODC inhibits low‐dose UVB‐induced autophagy, whereas it induces autophagy in response to high‐dose UVB but prevents cellular apoptosis. ODC protects cells from apoptosis caused by high‐dose UVB radiation via an autophagic survival mechanism. Through the Atg12 protein, ODC promotes autophagy and inhibits UVB‐induced cellular apoptosis.